Synthesis, crystal structure, characterization, and microbial evaluation of (E)-N-(4-isopropylbenzylidene)thiophene-2-carbohydrazide. (23rd May 2016) - Rajavel, A.; Jeyakumar, T.; Sundararajan, M. L.; Srinivasan, T.; Velmurugan, D.
ABSTRACT: ( E )- N -(4-isopropylbenzylidene)thiophene-2-carbohydrazide (L) was prepared and characterized using elemental analysis, UV-visible, IR, 1 H and 13 C NMR, mass spectra. The crystal structure of L was determined by single-crystal X-ray diffraction method. The compound L crystallizes in monoclinic space group P 21 / n with a = 16.676(5) Å, b = 5.475(5) Å, c = 17.022(5) Å, and Z = 4. Antimicrobial and antifungal activity was assayed against four bacterial and four fungal microorganisms. The antioxidant behavior of L was also investigated. GRAPHICAL ABSTRACT: Highlights ▪ A new hydrazide with thiophene moiety has been synthesized and characterized by spectral techniques. ▪ The compound was also characterized by single-crystal X-ray diffraction technique. ▪ Antimicrobial and antioxidant activity of the compound were tested.